Application of Monte Carlo techniques with delay-time analysis to assess maintenance and inspection policies for marine systems. (April 2017) - McNamara, D; Cunningham, A; Riahi, R; Jenkinson, I; Wang, J
This paper presents a novel methodology applying Monte Carlo methods with delay-time analysis to test the effects of scheduled maintenance and inspection actions on factors affecting the operational efficiency of a marine system which is subject to degradation. The aim is to demonstrate how a Monte Carlo model incorporated into delay-time analysis can be used to predict the transition behaviour of a system under analysis. The model presented in this paper focuses on the effects on system failure probability and downtime of various maintenance and inspection policies. The impact on spare part requirements is also investigated.